Cardiac involvement in myotonic dystrophy: The role of troponins and N-terminal pro B-type natriuretic peptide. (December 2017) - Valaperta, Rea; De Siena, Claudia; Cardani, Rosanna; Lombardia, Fortunata; Cenko, Edina; Rampoldi, Benedetta; Fossati, Barbara; Brigonzi, Elisa; Rigolini, Roberta; Gaia, Paola; Meola, Giovanni; Costa, Elena; et al.
Abstract: Background and aims: Myotonic dystrophy type 1 (DM1) and type 2 (DM2) are dominant inherited muscular dystrophies with multiple systemic involvement, often producing cardiac injury. This study sought to determine the clinical significance of elevated high sensitivity cardiac troponin T and I (hs-cTnT and hs-cTnI), and N-terminal pro B-type natriuretic peptide (NT-pro-BNP) in this population. Methods: Sixty DM patients (35 men and 25 women; mean age: 45.1 years, range: 12–73 years) underwent clinical cardiac investigations and measurements of serum hs-cTnT, hs-cTnI, creatine kinase (CK), and NT-proBNP. Left ventricular (LV) ejection fraction (EF) was assessed by echocardiography. Results: Genetic analysis revealed that 46 of the 60 patients were DM1, and 14 DM2. Blood measurements showed persistent elevation of hs-cTnT and CK in 55/60 DM patients (91.73%). In contrast, hs-cTnI values were persistently normal throughout the study. Only 2 patients showed an EF <50%, being the overall range of this population between 40% and 79%. We found ECG abnormalities in 19 patients. Of these patients, 13 showed first or second-degree atrio ventricular (AV) blocks (PR interval ≥ 200 ms), 4 showed a left bundle branch block (LBBB) prolonged (QRS duration ≥120 ms), and 2 had an incomplete bundle branch block (QRS duration between 110 and 119 ms). After excluding patients with EF <50%, NT-pro-BNP measurement > 125 pg/mL was an independent predictor of ECG abnormalities. Conclusions: NT-pro-BNP levels may be considered to be used clinically to identify DM patients at increased risk of developing myocardial conduction abnormalities. Highlights: Myotonic dystrophy (DM) is a progressive multisystem disorder characterized by myotonic myopathy. Data on cardiac involvement are needed to determine the incidence of cardiac complications and their prognostic implications in DM population. Biomarkers could be useful to identify DM patients with similar disease course. NT-proBNP may be an indicator of myocardial conduction abnormalities in patients with DM. Further studies with larger sample size and longer follow-up are needed to confirm the hypothesis.